2021
DOI: 10.1038/s41389-021-00363-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p53 suppresses replication stress-induced DNA damage in ATRX-deficient neuroblastoma

Abstract: Genetic aberrations are present in the ATRX gene in older high-risk neuroblastoma (NB) patients with very poor clinical outcomes. Its loss-of-function (LoF) facilitates the alternative lengthening of telomeres (ALT) pathway in tumor cells and is strongly linked to replication stress (RS) and DNA damage through G-quadruplex (G4) DNA secondary structures. However, limited information is available on ATRX alteration-related NB tumorigenesis. We herein knocked out (KO) ATRX in MYCN-amplified (NGP) and MYCN single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…The RS response shares many biological pathways with DDR. They are widely intertwined and thus hard to completely distinguish (124). Here, we grouped the proteins that are typically related to the DDR pathway but are not necessarily involved in the RS response.…”
Section: Targeting Rs-induced Ddrmentioning
confidence: 99%
“…The RS response shares many biological pathways with DDR. They are widely intertwined and thus hard to completely distinguish (124). Here, we grouped the proteins that are typically related to the DDR pathway but are not necessarily involved in the RS response.…”
Section: Targeting Rs-induced Ddrmentioning
confidence: 99%
“…Studies found higher replication levels of stress and damage to telomeres compared to telomerase-dependent tumour cells, which is thought to be an activation signal of the ALT pathway and can promote elongation of ALT telomeres [ 37 ]. Numerous studies show that there are multiple sources of replication stress in ALT cells and that these cells are more likely to accumulate replication stress [ 11 , 12 , 13 , 38 , 39 ].…”
Section: Source Of Replication Stress Of the Alt Telomeresmentioning
confidence: 99%
“…ALT can be engaged in a wide range of tumor types, and is a common telomere-lengthening mechanism among certain sarcomas (e.g., osteosarcomas and liposarcomas), as well as in subsets of central nervous system tumors, including astrocytomas; however, ALT is relatively rare in the epithelial malignancies [10]. Adopting the ALT pathway confers many unique molecular characteristics to tumors, some of which are commonly used as markers of ALT activity, including (1) high-frequency ATRX mutations, (2) abundant telomeric secondary structures such as R-loops, G4-quadruplexes and telomeric fragility such as extrachromosomal Telomere Repeat (ECTR), (3) active telomeric sister chromatid exchange (T-SCE), (4) ALT-associated PML bodies (APBs) and (5) heterogeneous telomere length [8,9,[11][12][13]. The accumulation of R-loops and G-quadruplexes at telomeres may impede the progression of DNA replication, leading to the collapse of replication forks and the formation of one-ended DSBs, which activate BIR-independent telomeric DNA synthesis, consist of DNA end reaction for the formation of 3 hangout, RAD51/RAD52-dependent invastion, telomere extension mediated by polδ or polη, and Holliday junction resolution named D-loop resolution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Many other genes or pathways have been identified that can explain the extremely divergent and heterogeneous clinical phenotypes of NB, including telomerase maintenance mechanisms, the adrenergic or mesenchymal developmental origin and the presence of ALK-RAS or TP53 pathway mutations. [12][13][14] In the last decades, the association between many potential oncogenes and patient's survival has been largely investigated. [15][16][17] A recent study reported a high expression of E2 transcription factor 3 (E2F3) in association with poor survival in NB patients with a normal MYCN copy number diagnosed in stage 4S.…”
Section: Introductionmentioning
confidence: 99%
“…The main recognised prognostic factors include metastatic disease, age >18 months, recurrent segmental chromosomal aberrations (SCA) and/or genomic amplification of the proto‐oncogene MYCN 6–11 . Many other genes or pathways have been identified that can explain the extremely divergent and heterogeneous clinical phenotypes of NB, including telomerase maintenance mechanisms, the adrenergic or mesenchymal developmental origin and the presence of ALK‐RAS or TP53 pathway mutations 12–14 …”
Section: Introductionmentioning
confidence: 99%